How high (low) are the possibilities of teleworking in Mexico? - Gustavo Leyva; Israel Mora (Banco de México, 2021)
We estimate that about 10.6 percent of jobs could be done from home in Mexico, using 468 4-digit SINCO occupations and employment data in 2019. This is roughly half the estimate reported by Dingel and Neiman (2020) using teleworking criteria devised for the U.S. labor market. Owing to the peculiarities of the Mexican labor market, we report results by type of contract (formal and informal), geographical area, and gender. We validate our teleworking measure by exploiting the cross-state variation of real GDP per worker, the share of services in employment, and internet and computer access within the household. We find that the gap in teleworking possibilities favorable to females has its root in the disparate occupation structures across gender. During the pandemic, the decline in the share of non-telework jobs in females has been thrice as much as that in males.
Keywords: J16; J46; J81; 330; COVID-19; teleworking; informality; information and communication technologies; gender; Mexico; states; regions